Evaluation of Corporate Bond Market Performance in Bangladesh - Alam, Abu Hanifa Md Noman Bin; Islam, Serajul; Chy, Nazneen Jahan (IIUC Studies, 2016)
Bond market plays a vital role in economic development of a country. Bond market provides long term finance to issuers by creating alternative source of finance through stock market, besides providing stable source of income to investors against volatile stock market. However, Bangladesh corporate Bond market is at very initial stage. Hence, it is needed to make an analysis of investors attitude towards corporate bonds in Bangladesh for determining investors finding on the issue. The study is limited to performance evaluation of three corporate bonds in corporate bond market in Bangladesh and investigate investors attitude towards it. We have collected secondary information from DSE web site and processed through SPSS to make performance analysis and collected primary data from investors of some brokerage houses in Chittagong metro through questionnaire survey for analyzing investors attitude towards corporate bond market. The study has found that price stability of ACI zero coupon bond is more than IBBL Perpetual Mudaraba Bond and BRAC subordinated convertible bond and it is also found that only 5% of respondents prefers to invest in corporate bonds due to lack of supply of corporate bond, lack of investors awareness, inadequate market regulations etc. IIUC Studies Vol.10 & 11 December 2014: 127-144